A History of 1970s Experimental Film - Gaal-Holmes, P. author. aut Link
XVIII, 231 p.
Keywords: This comprehensive historical account demonstrates the rich diversity in 1970s British experimental filmmaking, acting as a form of reclamation for films and filmmakers marginalized within established histories. An indispensable book for practitioners, historians and critics alike, it provides new interpretations of this rich and diverse history.